The Prison Houses of Knowledge: Activist scholarship and revolution in the era of “globalization” - D’Souza, Radha (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThe rise of new social movements has produced an emerging discourse on activist scholarship. There is considerable ambiguity about what the term means. In this article I draw on my work as a trade unionist, political activist, and activist lawyer in Mumbai, and later as a social justice activist in New Zealand to reflect on the meaning of activist scholarship, interrogate the institutional contexts for knowledge, and the relationship of knowledge to emancipatory structural social transformations. Although based on personal experiences, this article provides a theoretically oriented meta-analysis of activist scholarship.